2001
DOI: 10.1128/jb.183.4.1385-1393.2001
|View full text |Cite
|
Sign up to set email alerts
|

Fnr Is Required for NifL-Dependent Oxygen Control of nif Gene Expression in Klebsiella pneumoniae

Abstract: In Klebsiella pneumoniae, NifA-dependent transcription of nitrogen fixation (nif) genes is inhibited by NifL in response to molecular oxygen and combined nitrogen. We recently showed that K. pneumoniae NifL is a flavoprotein, which apparently senses oxygen through a redox-sensitive, conformational change. We have now studied the oxygen regulation of NifL activity in Escherichia coli and K. pneumoniae strains by monitoring its inhibition of NifA-mediated expression of K. pneumoniae ø(nifH-lacZ) fusions in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 41 publications
1
42
1
Order By: Relevance
“…Nitrogen-fixing microorganisms developed several strategies to deal with this dilemma. Both Klebsiella pneumonia, an anaerobe, and A. vinelandii, an aerobe, monitor oxygen levels using the NifA transcriptional regulator that controls nitrogen fixation (29,30). Many other prokaryotes also regulate the expression of nitrogen-fixation genes in response to oxygen concentration and energy availability.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen-fixing microorganisms developed several strategies to deal with this dilemma. Both Klebsiella pneumonia, an anaerobe, and A. vinelandii, an aerobe, monitor oxygen levels using the NifA transcriptional regulator that controls nitrogen fixation (29,30). Many other prokaryotes also regulate the expression of nitrogen-fixation genes in response to oxygen concentration and energy availability.…”
Section: Discussionmentioning
confidence: 99%
“…We could not use the fulllength NifA protein in these experiments since it has no activity in E. coli (25,26). On the other hand, as expected, the K. pneumoniae NifA protein was fully active under all conditions tested, including in the fnr mutant (Table 2), since it is not directly sensitive to oxygen or directly dependent on fnr (10). Immunoblot analysis (23) of the N-truncated NifA protein produced from pRAM7 in extracts of cells grown under the same conditions showed that the lack of NifA activity in the fnr strain JRG1728 corresponded to the absence of the N-truncated NifA protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, sodium dithionite can reduce NifL of A. vinelandii in vivo, resulting in a protein unable to complex NifA. Although the in vivo NifL-reducing and -oxidizing species have not been defined yet (10,18,23), it has been suggested that a heme protein may be involved (13). The NifA proteins from rhizobia, A. brasilense, and H. seropedicae are not active in the presence of high oxygen concentrations and require iron for in vivo activation of nif gene promoters, suggesting that the NifA proteins of this class may sense oxygen directly (2,32,9,25).…”
mentioning
confidence: 99%
“…One candidate iron-containing protein that acts as a general oxygen sensor is the global regulator Fnr, which contains an oxygen-labile [4Fe-4S] cluster (52). Analysis of the K. pneumoniae NifL-NifA system in fnr mutants of E. coli and K. pneumoniae indicated that Fnr is required to maintain Kp NifL in a noninhibitory state under anaerobic, nitrogen-limiting conditions (36). Since Fnr is unlikely to be a direct electron donor to Kp NifL, the physiological electron donor is likely to be an electron transport component encoded by a gene(s) that is subject to transcriptional activation by Fnr under anaerobic conditions.…”
Section: Redox-oxygen Sensingmentioning
confidence: 99%